Wider geographic distribution and higher diversity of hexaploids than tetraploids in Carassius species complex reveal recurrent polyploidy effects on adaptive evolution - Xiao-Li Liu (Nature Portfolio, 2017)
Abstract Polyploidy roles on adaptive evolution and ecological novelty have been extensively studied in plants but remained unclear in vertebrates owing to the rare polyploidy incidences. Here, a huge number of 3105 specimens in Carassius species complex including 2211 hexaploids and 894 tetraploids were sampled from 34 locations through mainland China. And hexaploids had wider geographic distribution than tetraploids especially in the areas with high altitude, high latitude and low annual precipitation. Then, an approximate 1050 bp transferrin (tf) fragments were amplified from all the samples, and 526 tf alleles were identified from a total of 37260 sequences at last. Intriguingly, higher nucleotide diversity of tf alleles in hexaploids than in tetraploids was revealed. Moreover, via phylogenetic analysis of tf alleles, potential origin center of Carassius species complex was deduced to be Yangtze River basin and hexaploids should undergo multiple independent polyploidy origins from sympatric tetraploids. These findings indicate that the hexaploids might possess stronger environmental adaptation and ecological novelty than the tetraploids, which provide an association paradigm of recurrent polyploidy and ecological context in polyploid vertebrates.